Review of Darwin and the Emergence of Evolutionary Theories of Mind and Behavior, by Robert Richards - Dennett, Daniel C. (Tufts Archival Research Center, 2005)
Dennett, Daniel C. "Review of Darwin and the Emergence of Evolutionary Theories of Mind and Behavior, by Robert Richards." Philosophy of Science 56, no. 3 (1989): 540-43.